IDENTIFIKASI ZONASI POTENSI AIR TANAH DI WILAYAH KEKERINGAN BERBASIS SISTEM INFORMASI GEOGRAFIS - Rusdi, Rusdi (Indonesian Journal of Applied Geography, 2024)
The drought disaster that has hit Indonesia in recent years has caused several regions to experience drought impacts. Laikang Village is one of the villages affected by drought with limited water availability and clean water. Groundwater is one of the potential clean water that can be used to meet these needs. This study aims to find out the zoning of groundwater potential in Laikang Village and the factors that affect it. This research utilizes data using the Geographic Information System method. The results of this study show that the zoning of groundwater potential in Laikang Village consists of four categories: the Very Low Groundwater Potential Zone covers 2.01 hectares (0.12%), the Low Groundwater Potential Zone covers 1093.79 hectares (66.91%), the Medium Groundwater Potential Zone covers an area of 428.09 hectares (26.19%), and the High Groundwater Potential Zone covers 110.83 hectares (6.78%). Low-potential zones dominate this region.